The development of a family liaison team to improve communication between intensive care unit patients and their families during the COVID-19 pandemic. Issue 6 (27th November 2020) - Gabbie, Susie; Man, Kin; Morgan, Gareth; Maity, Santanu
Abstract : A family liaison team was developed to improve communication between intensive care unit patients and their families during the COVID-19 pandemic.